REKAYA PENGGUNAAN INFORMASI AKUNTANSI DEFERENSIAL DALAM PENGAMBILAN KEPUTUSAN UNTUK MENINGKATAN LABA JANGKA PENDEK PADA UKM DI BOJONEGORO - Hasan Bisri (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2018)
Small and Medium Businesses (SMEs) that are able to survive in conditions of unstable economy need to create strategies in penentukan short term profit, in the determination of short-term profit is almost all using traditional methods in determining profit . Method of the determination of profit with the traditional system that is in use by SMES've not relefan again to increase profits, this method is already being used in I920 's and has left the company by Japan after World War II and in the follow United 20 years later senagai the State winner of the war. On bicycle storage services company Independent's son is still using traditional methods in cost will be loaded on consumers still use general costs charged to users of the service, its place next to the terminal of Bojonegoro, consumers Choose a strategic place, because the facilities are still impressed with what it is still land and building conditions also still not perfect. In addition the use of differential accounting information is very beneficial against the management of the chicken noodle to bloom Sari in obtaining the information needed to be able to compare which more favorable decisions among buy or make own noodles. Comparison of the calculation of the costs incurred by the two alternatives showed that produces itself is a more appropriate decision because getting the profit differential greater than on buying from outside. By using the information differensial has been known to create their own alternative that can save you the cost of making the noodles.